Dental calculus: A repository of bioinformation indicating diseases and human evolution - Li, Qinyang; Luo, Kaihua; Su, Zhifei; Huang, Fangting; Wu, Yajie; Zhou, Fangjie; Li, Yuqing; Peng, Xian; Li, Jiyao; Ren, Biao (Frontiers in Cellular and Infection Microbiology, 2022)
Dental calculus has long been considered as a vital contributing factor of periodontal diseases. Our review focuses on the role of dental calculus as a repository and discusses the bioinformation recently reported to be concealed in dental calculus from three perspectives: time-varying oral condition, systemic diseases, and anthropology at various times. Molecular information representing an individual’s contemporary oral health status could be detected in dental calculus. Additionally, pathogenic factors of systemic diseases were found in dental calculus, including bacteria, viruses and toxic heavy metals. Thus, dental calculus has been proposed to play a role as biological data storage for detection of molecular markers of latent health concerns. Through the study of environmental debris in dental calculus, an overview of an individual’s historical dietary habits and information about the environment, individual behaviors and social culture changes can be unveiled. This review summarizes a new role of dental calculus as a repository of bioinformation, with potential use in the prediction of oral diseases, systemic diseases, and even anthropology.